2021
DOI: 10.1186/s13018-021-02580-6
|View full text |Cite
|
Sign up to set email alerts
|

Clinical observation and finite element analysis of cannulated screw internal fixation in the treatment of femoral neck fracture based on different reduction quality

Abstract: Objective Femoral neck fracture is one of the most common bone types. The effect of reduction quality on hip joint function and complications after screw internal fixation is not fully understood. To investigate the clinical efficacy and mechanical mechanism of positive buttress, anatomical reduction, and negative buttress in the treatment of femoral neck fracture after cannulated screw fixation. Methods Retrospective analysis of patients with femo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 33 publications
1
21
0
Order By: Relevance
“…The traditional fixation of 3CS in an inverted triangle configuration has always been controversial in the treatment of unstable FNFs due to poor mechanical stability [35]. Previous studies have shown a high incidence of hip varus deformity and femoral neck shortening after 3CS fixation [23,36,37], increasing the risk of internal fixation failure and revision via arthroplasty [38]. The results of our study support previous findings.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The traditional fixation of 3CS in an inverted triangle configuration has always been controversial in the treatment of unstable FNFs due to poor mechanical stability [35]. Previous studies have shown a high incidence of hip varus deformity and femoral neck shortening after 3CS fixation [23,36,37], increasing the risk of internal fixation failure and revision via arthroplasty [38]. The results of our study support previous findings.…”
Section: Discussionsupporting
confidence: 88%
“…Firstly, the finite element analysis assumes that the object of study is a homogeneous material and sets material properties using uniform modulus of elasticity and Poisson's ratio, which can be somewhat different from the actual condition. In addition, the prognosis of femoral neck fractures treated by internal fixation is closely related to the quality of reduction [23], but our study simulated a fully anatomically repositioned Pauwels type III FNF, which is not always the case in clinical practice. As mentioned above, there are various configurations of 3CS and only traditional inverted triangle configuration included in this study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple attempts of closed reduction or open reduction with the aim of anatomical reduction can damage the blood supply of the femoral head and increase the incidence of fracture nonunion or necrosis of the femoral head [ 12 ]. Recently, nonanatomical reductions of FNF, which include positive buttress reduction and negative buttress reduction, have attracted wide attention [ 13 15 ]. The definition of the former is that the distal fracture segments is positioned medially to the lower-medial edge of the proximal segment, while the latter is that the proximal fracture segment is positioned medially to the upper medial edge of the distal segment [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…The definition of the former is that the distal fracture segments is positioned medially to the lower-medial edge of the proximal segment, while the latter is that the proximal fracture segment is positioned medially to the upper medial edge of the distal segment [ 16 ]. Since Gotfried et al first proposed the concept of nonanatomical reduction in 2013, numerous studies have compared the effect of nonanatomical reduction and anatomical reduction in FNF [ 10 , 13 15 ]. However, all of these studies focused on internal fixation with CCS.…”
Section: Introductionmentioning
confidence: 99%